The novel H2VK-65 clinical risk assessment tool predicts high coronary artery calcium score in symptomatic patients referred for coronary computed tomography angiography - Kaolawanich, Yodying; Prapan, Natthaporn; Phoopattana, Supamongkol; Boonyasirinant, Thananya (Frontiers in Cardiovascular Medicine, 2023)
Background: Coronary computed tomographic angiography (CCTA) has emerged as a powerful imaging modality for the detection and prognostication of individuals with suspected coronary artery disease (CAD). High amounts of coronary artery calcium (CAC) significantly obscure the interpretation of CCTA. Clinical risk assessment tools and data specific to predictors of high CAC in symptomatic patients are limited. Methods: Consecutive patients who underwent CAC scan and CCTA to diagnose CAD during 2016-2020 were included. A high CAC score was defined as >400 by Agatston method. Univariate and multivariate analyses were performed to determine the predictors of high CAC. The clinical risk score was derived from factors independently associated with high CAC. The derivation cohort was composed of 465 patients; this score was validated in 98 patients. Results: The mean age was 63±11 years, 53% were female, and 15.9% had high CAC scores. The independent predictors of high CAC scores were age >65 years (odds ratio [OR] 3.02, 95% confidence interval (95%CI) 1.56-5.85, p=0.001), chronic kidney disease (CKD) (OR 11.09, 95%CI 3.38-36.38, p<0.001), heart failure (OR 6.52, 95%CI 2.23-19.09, p=0.001), hypertension (OR 26.44, 95%CI 9.02-77.44, p<0.001), and vascular diseases, including ischemic stroke/transient ischemic attack and peripheral arterial disease (OR 20.96, 95%CI 4.19-104.86, p<0.001). The H2VK-65 (Hypertension, Heart failure, Vascular diseases, CKD, and Age>65) score allocates 1 point for age >65, 2 points for CKD or heart failure, and 3 points for hypertension or vascular diseases. Using a threshold of ≥4 points, the sensitivity and specificity to detect high CAC was 81% and 80%, respectively. The area under the curve was 0.88 and 0.85 in the derivation and validation cohorts, respectively. Conclusion: The novel H2VK-65 score demonstrated good performance for predicting high CAC scores in symptomatic patients referred for CCTA.